HERPETOFAUNA OBSERVATIONS FOR CONSERVATION: INSIGHTS FROM JHUMPA LAHIRI AND CELESTE NG. - A. Asha Manorah Jenefer, Dr. T. Sri Devi (Chelonian Research Foundation, 2023)
Abstract For the purpose of conservation efforts, this article emphasises the significance of herpetofauna observation and communication. The study starts by tracing the development of herpetofauna observation, defining that term, and introducing two novels, The Lowland, by Jhumpa Lahiri and Little Fires Everywhere by Celeste Ng, and how they depict herpetofauna observation. The paper gives background information on Subhash and Mia and describes how their research and observations are depicted in the novels. It examines the effects of their findings on conservation planning and management and notes the parallels and discrepancies between the two portrayals. The article's conclusion emphasises the necessity of interpersonal relationships and communication in motivating people to preserve the environment, as well as the significance of observing and monitoring herpetofauna populations for conservation efforts. Keywords: Amphibians, Reptiles, Ecology, Biodiversity, Wildlife management, Conservation, etc.,